The Effect of Blended Learning by Using Edmodo in Teaching English for Nursing Students - Laili, Roudlotun Nurul; Nashir, Muhammad (Curriculum and Educational Technology Department, 2018)
Due to the developments of social networking in education, teachers have to provide the innovative techniques and select the best way in teaching learning process in classroom, especially in learning English as a foreign language so that the students are interested and eager to learn English. Edmodo as one of online learning media is believed to present an eﬀective solution in the teaching English. This research investigates the eﬀectiveness of blended learning by using Edmodo in teaching English for nursing students. This research used quasi experimental research design. It begins from conducting homogeneity test, deciding the experimental group and control group. Then, it was continued by giving activities to the control class using face to face learning and giving treatments to the experimental class that was using blended learning (combine face to face learning with online learning/Edmodo), then giving the same post-test to both classes. The result indicated that there was a signifcant eﬀect of teaching English in blended learning by using Edmodo on nursing students. It is proved by the value of signifcant column of t-test table and the result is 0.000 which was lower than 0.05. Abstrak  Seiring perkembangan jejaring sosial dalam pendidikan, guru harus memberikan teknik inovatif dan memilih cara terbaik dalam proses pembelajaran di kelas, terutama dalam belajar bahasa Inggris sebagai bahasa asing sehingga siswa tertarik dan bersemangat untuk belajar bahasa Inggris. Edmodo sebagai salah satu media pembelajaran online diyakini menghadirkan solusi efektif dalam pengajaran bahasa Inggris. Penelitian ini mengkaji efektivitas pembelajaran campuran dengan menggunakan Edmodo dalam mengajar bahasa Inggris untuk mahasiswa keperawatan. Penelitian ini menggunakan desain penelitian quasi experimental. Dimulai dari melakukan uji homogenitas, menentukan kelompok eksperimen dan kelompok kontrol. Kemudian dilanjutkan dengan memberikan treatmen kepada kelas kontrol menggunakan pembelajaran tatap muka dan perlakuan ke kelas eksperimen yaitu menggunakan blended learning (menggabungkan pembelajaran tatap muka dengan pembelajaran online/Edmodo), kemudian memberikan post-test yang sama untuk keduanya. Hasil menunjukkan bahwa ada pengaruh yang signifkan dari kombinasi mengajar tatap muka dengan Edmodo terhadap kemampuan bahasa Inggris mahasiswa keperawatan. Hal ini dibuktikan dengan nilai kolom tabel t-test yang signifkan dan hasilnya adalah 0.000 yang lebih rendah dari 0.05 Keywords:  Edmodo; Blended Learning; Teaching English